Potential Use of Direct Current Electric Fields to Eradicate Rainbow Trout Embryos from Freshwater Ecosystems. (11th September 2015) - Gross, Jackson; Farokhkish, Bahram; Cornacione, Matthew; Shaw, Steven; Nguyen, Phong L.; Henry, Theodore B.
Abstract: The application of electric fields (i.e., electroshocking) may be an option in the eradication of invasive freshwater fishes. Electric fields can be used to facilitate capture or to kill vulnerable life history stages of fish. The objective of this study was to evaluate the relations between water conductivity and the electrical variables of voltage gradient and power density on the mortality of Rainbow Trout Oncorhynchus mykiss embryos at different developmental stages. Embryos in age‐groups ranging from 27 to 405 daily temperature units (TU) were exposed for 5 s to constant (nonpulsed) DC electric fields (2–20 V/cm) at a water conductivity of 220 S/cm to determine (1) the stage of embryonic development most susceptible to electroshock‐induced mortality, and (2) the lethal voltage gradient (V/cm) predicted to kill 50% (LV50) of embryos in each age‐group. Mortality was assessed 24 h postexposure. Using LV50 voltages determined for each age‐group, the relation between water conductivity (20–640 S/cm) and electroshock‐induced mortality from exposure to LV50 was determined for six different stages of embryonic development (81–364 TU). Results show that the mortality of embryos exposed to electroshock decreased with the stage of embryonic development. The mortality of embryos exposed to the LV50 for their respective age‐groups increased with water conductivity and was consistent throughout early development (81–292 TU), but the effects of increased conductivity were not observed in eyed embryos after 364 TU, as mortality remained constant with the determined LV50 values. Voltage was determined to be the most influential factor of embryo mortality. As conductivity increased, maintaining a constant voltage (LV50) elicited greater mortality than maintaining a constant power. These data suggest that a combination of DC electric field and increased localized conductivity could be effective at eradicating nuisance salmonids prior to eyed embryonic stages. Received March 18, 2015; accepted June 3, 2015